FORMING A MANAGERIAL TEAM FOR STRENGTHENING POTENTIAL OF AN ENTERPRISE ECONOMIC SECURISTY SYSTEM (Development Service Industry Management, 2025)
Concept of potential in a general scientific sense, as well as an enterprise's economic security system are examined. That allowed proposing an interpretation of a concept of potential of the enterprise's economic security system. Organization of a team aimed at strengthening potential of the enterprise's economic security system is proposed based on identified components, in particular: a defined position within an organizational structure of an enterprise, providing rhythm, regularity, and consistency of activity, and ensuring complementarity and coordinated actions of the team members.To enhance potential of the enterprise's economic security system, it is proposed to form a group composed of representatives from different departments of the enterprise. Such an approach will ensure the interdisciplinary and comprehensive nature of the group’s work. Providing the rhythm, regularity, and consistency of this group’s work should be supported by its regular meetings with planning and reporting on achieved results. To ensure complementarity and coordinated actions of the team members in strengthening the economic security system’s potential, it is recommended to use R. Belbin’s well-known team role model. Each team member’s tasks are defined in the context of enhancing potential of the enterprise's economic security system.Three fundamentally different tasks for strengthening potential of the enterprise's economic security system are identified — organizing the team’s work and coordinating efforts of its members; developing and analyzing ideas, formulating proposals; implementing planned actions and carrying out specific activities. A corresponding distribution of these tasks is proposed among the team members (according to R. Belbin).To simplify and accelerate strengthening of the enterprise's economic security system potential, specific types of support are suggested. These types of support include consulting, informational, training and educational, financial and material, change management, and relational support. For each proposed type of support its essence is described, its necessity is substantiated, and expected consequences of its absence are outlined.
Keywords: enterprise economic security system; potential; management team; team members; organizational components; support